Effects of different kinds and concentrations of fatty acids on differentiation and development of cotton fiber - Sun Yingchao; Liu Wei; He Qiuling; Zhu Shuijin; Chen Jinhong (浙江大学学报. 农业与生命科学版, 2014)
As a kind of seed fiber, cotton fiber was differentiated by epidermal cells of the seed, and was adhered to seed surface. Cotton kernel is rich in fat, protein and other ingredients. However, whether these ingredients affect the differentiation and development of cotton fiber, and subsequently influence the yield and quality has become a hot topic in the related research area recently. It also has a pivotal role in the regulation to cotton production and quality formation.For exploring the function of fatty acid in the developing process of cotton fiber, this study took upland cotton standard system TM-1 as experimental material, to investigate the effect of different kinds of fatty acids on fiber differentiation and development along with fiber length. The experiment was conducted by adding 5.0 μmol/L different kinds of fatty acids respectively (including nutmeg acid, palmitic acid, stearic acid, oleic acid, linoleic acid, peanut acid, docosanoic acid and wood wax acid,) in the in vitro ovule culture medium. These fatty acids were with varied chain length. The medium without any fatty acid was involved as a control. Scanning electron microscope (SEM) was used to observe the differential and developmental situation of ovule surface after 2 d culture, and the fiber length was measured after 2 weeks. Thereafter, the palmitic acid was selected to study the effect of concentration gradient on fiber development; in other words, different palmitic acid concentrations of 0.01, 0.1, 1.0, 5.0, 10.0, 20.0, 25.0, 30.0 μmol/L were added into medium to investigate their effects on the differentiation and development of cotton fiber by using SEM and length measurement.The results showed that in the medium with 5.0 μmol/L palmitic acid, ovule epidermal ridges were much more dense and well-distributed than in the control and the other treatments. Almost no ridge was observed in the treatments of stearic acid, oleic acid and docosanoic acid. The fiber length measured in the treatments of palmitic acid (being 1.086 mm) and wood wax acid (being 0.863 mm) was increased by 53.4% and 21.9% compared with the control respectively. However, no significant difference was found between the control and the other treatments. The result also showed that 5.0 μmol/L palmitic acid in the medium was the most optimal concentration to promote the fiber differentiation and development, likewise to facilitate the fiber elongation.According to the results, it is preliminary deduced that the palmitic acid has remarkably positive effects on the cotton fiber differentiation, development and elongation. This consequence provides an evidence to the research of regulating cotton fiber differentiation and development as well as the production and quality formation by altering the composition and/or concentration of cottonseed fatty acid.